2005
DOI: 10.1093/ndt/gfi175
|View full text |Cite
|
Sign up to set email alerts
|

Effect of haemodialysis on signal-averaged electrocardiogram P-wave parameters

Abstract: Our study revealed that P-wave SAECG parameters are abnormal in a significant portion of HD patients and improved with HD process. We have also demonstrated that patients' age, volume status as well as the presence of anaemia are important factors influencing P-wave SAECG parameters in HD patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
11
2

Year Published

2006
2006
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 19 publications
4
11
2
Order By: Relevance
“…In others, changes were not detected or were seen only at the conclusion of dialysis and then quickly attenuated (52). However, in one study, P-wave duration decreased and root mean square voltage of the final 20 ms of the filtered P wave decreased from the beginning to the end of dialysis, changes suggesting a reduced risk of AF after HD (53). Changes in electrolytes were associated with P-wave parameters in several studies (51,52), but associations with ultrafiltration appear more robust (50,51).…”
Section: Dialysis As a Triggermentioning
confidence: 94%
“…In others, changes were not detected or were seen only at the conclusion of dialysis and then quickly attenuated (52). However, in one study, P-wave duration decreased and root mean square voltage of the final 20 ms of the filtered P wave decreased from the beginning to the end of dialysis, changes suggesting a reduced risk of AF after HD (53). Changes in electrolytes were associated with P-wave parameters in several studies (51,52), but associations with ultrafiltration appear more robust (50,51).…”
Section: Dialysis As a Triggermentioning
confidence: 94%
“…Similar risk factors have also been suggested for the development of atrial fibrillation in HD patients (3,4). However, there are still conflicting data about the effect of HD, and various dialysis composition and dialysis protocols on the occurrence of atrial arrhythmias in HD patients (6)(7)(8).…”
mentioning
confidence: 68%
“…In HD patients, many of the reports on SAECG parameters are focused exclusively on ventricular SAECG (12)(13)(14). To the best of our knowledge, P-SAECG has been investigated only in a study of Jaroszynski et al (6), and it needs to be elucidated further.…”
mentioning
confidence: 99%
“…We did not find any significant change in P max durations throughout the HD session. Similarly, Jaroszyński et al [14] reported that HD process induced a significant decrease in the filtered P wave duration. However, Szabo et al [8] and Tezcan et al [9] reported that maximum P wave durations increased after dialysis compared with measurements before dialysis, resulting in an increase in PWD.…”
Section: Discussionmentioning
confidence: 89%